Peran Keluarga dalam Membentuk Karakter Remaja pada Masa Pubertas melalui Pendekatan Pendidikan Agama Islam - Hanifah, Najwa Nur; Hanif, Ma'mun (Jurnal el-Huda, 2025)
This study aims to examine the role of the family in shaping the character of adolescents during puberty through an Islamic religious education approach. The study uses a qualitative method with a case study approach, involving families with adolescents aged 12-18 years. The findings show that the family plays a significant role in instilling moral and ethical values of Islam, which help adolescents face challenges such as social pressure and identity crises. Effective communication between parents and adolescents is a key factor in the success of this process. The study concludes that the consistent application of religious values within the family can foster a strong and positive character in adolescents.